Kriterii i dinamika special'noj rabotosposobnosti grebcov-akademistov v ontogeneze - Slautina, I. N. (Teorija i Praktika fiziceskoj Kul'tury, 2006)
The set of representative criteria which determine the level of special productivity is necessary for rational management of the training process. At the analysis of the age dynamics of the maximal productivity in boar racing, there were used the materials "Annual World Ranking" where the maximum achievements of athletes from the various countries of the world are given. The results are received in standard conditions at modeling the distance of 2000 m on the "Concept II".